Outcomes of Breast Cancer Patients Treated with Chemotherapy, Biologic Therapy, Endocrine Therapy, or Active Surveillance During the COVID-19 Pandemic. (4th February 2022) - Marks, Douglas K; Budhathoki, Nibash; Kucharczyk, John; Fa'ak, Faisal; D'Abreo, Nina; Kwa, Maryann; Plasilova, Magdalena; Dhage, Shubhada; Soe, Phyu Phyu; Becker, Daniel; Hindenburg, Alexander; Lee, Johanna; et al.
Abstract: Purpose: Provide real-world data regarding the risk for SARS-CoV-2 infection and mortality in breast cancer (BC) patients on active cancer treatment. Methods: Clinical data were abstracted from the 3778 BC patients seen at a multisite cancer center in New York between February 1, 2020 and May 1, 2020, including patient demographics, tumor histology, cancer treatment, and SARS-CoV-2 testing results. Incidence of SARS-CoV-2 infection by treatment type (chemotherapy [CT] vs endocrine and/or HER2 directed therapy [E/H]) was compared by Inverse Probability of Treatment Weighting. In those diagnosed with SARS-CoV-2 infection, Mann–Whitney test was used to a assess risk factors for severe disease and mortality. Results: Three thousand sixty-two patients met study inclusion criteria with 641 patients tested for SARS-COV-2 by RT-PCR or serology. Overall, 64 patients (2.1%) were diagnosed with SARS-CoV-2 infection by either serology, RT-PCR, or documented clinical diagnosis. Comparing matched patients who received chemotherapy ( n = 379) with those who received non-cytotoxic therapies ( n = 2343) the incidence of SARS-CoV-2 did not differ between treatment groups (weighted risk; 3.5% CT vs 2.7% E/H, P = .523). Twenty-seven patients (0.9%) expired over follow-up, with 10 deaths attributed to SARS-CoV-2 infection. Chemotherapy was not associated with increased risk for death following SARS-CoV-2 infection (weighted risk; 0.7% CT vs 0.1% E/H, P = .246). Advanced disease (stage IV), age, BMI, and Charlson's Comorbidity Index score were associated with increased mortality following SARS-CoV-2 infection ( P ≤ .05). Conclusion: BC treatment, including chemotherapy, can be safely administered in the context of enhanced infectious precautions, and should not be withheld particularly when given for curative intent. Abstract : This article provides real-world data regarding the risk for SARS-CoV-2 infection and mortality in patients with breast cancer on active cancer treatment.